Exploring the Relationship Between Sleep Disturbances and Suicidal Ideation in Individuals with Post-Traumatic Stress Disorder (PTSD): A Cross-Sectional Study - Zahid Khan, Saqib Khalil, Seema Sharafat, Tariq Ali, Ijaz Aziz, Momin Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Post-Traumatic Stress Disorder (PTSD) is commonly coupled with sleep disorders that include sleeping disorders and nightmares, which have been verbosely addressed with suicidal thoughts. This relationship is very critical in determining what can be done to intervene and prevent suicides. Objective: To investigate the relationship between sleep disturbances and suicidal ideation among people with PTSD using a cross-sectional clinical study. Materials and Methods: This cross-sectional study was carried at Neurosurgery Department, Lady Reading Hospital Peshawar, Abbottabad Medical Complex, Mekran Medical College Turbat and Saidu Group of Teaching Hospital, Swat in the duration from May, 2022 to April, 2023. One hundred and sixty-seven PTSD patients have undergone the Pittsburgh Sleep Quality Index (PSQI) and the Columbia-Suicide Severity Rating Scale (C-SSRS). Analysis of data was carried out with SPSS v26. Results: Sleep disturbance was present in 75.4 per cent of respondents, in which insomnia and nightmares were significantly linked to suicidal ideation (p < 0.05). The strongest predictor was identified to be insomnia with an OR = 2.34 in logistic regression. Conclusion: Sleep disturbances, particularly insomnia and nightmares, are strongly correlated with suicidal ideation among PTSD patients. Keywords: PTSD, sleep disturbances, insomnia, suicidal ideation, nightmares, cross-sectional study.